Проектный синтез турбогенератора на основе численно-полевых расчетов при варьировании числа пазов статора - Милых, В.И (Електротехніка і електромеханіка, 2016)
Представлен пример проектного синтеза электромагнитной системы турбогенератора (ТГ) при его модернизации.
Создана математическая модель, связывающая новые и базовые параметры ТГ при изменении числа пазов статора.
Разработан скрипт Lua, обеспечивающий численно-полевые расчеты электромагнитных параметров ТГ в программной среде FEMM. Построение конструктивной и расчетной моделей, численно-полевые расчеты и выдача результатов выполняются компьютером автоматически, что обеспечивает высокую эффективность процесса проектирования ТГ. Апробация системы синтеза проведена на примере ТГ мощностью 340 МВт Представлено приклад проектного синтезу електромагнітної системи турбогенератора (ТГ) при його модернізації.
Створено математичну модель, що пов’язує нові та базові параметри ТГ при зміні кількості пазів статора. Розроблено скрипт Lua, який забезпечує чисельно-польові розрахунки електромагнітних параметрів ТГ в програмному середовищі FEMM. Побудова конструктивної та розрахункової моделей, чисельно-польові розрахунки та видача результатів виконуються комп'ютером автоматично, що забезпечує високу ефективність процесу проектування ТГ. Апробація системі проектного синтезу виконана на прикладі ТГ потужністю 340 МВт Purpose. The work is dedicated to the presentation of the principle of construction and implementation of an automated
synthesis system of the turbo-generator (TG) electromagnetic
system in the case of its modernization. This is done on the
example of changing the number of the stator core slots.
Methodology. The basis of the synthesis is a TG basic construction. Its structure includes the mathematical and physical-geometrical models, as well as the calculation model for
the FEMM software environment, providing the numerical
calculations of the magnetic fields and electromagnetic parameters of TG. The mathematical model links the changing
and basic dimensions and parameters of the electromagnetic
system, provided that the TG power parameters are ensured.
The physical-geometrical model is the geometric mapping of
the electromagnetic system with the specified physical properties of its elements. This model converts the TG electromagnetic system in a calculation model for the FEMM program.
Results. Testing of the created synthesis system is carried out
on the example of the 340 MW TG. The geometric, electromagnetic and power parameters of its basic construction and
its new variants at the different numbers of the stator slots are
compared. The harmonic analysis of the temporal function of
the stator winding EMF is also made for the variants being
compared. Originality. The mathematical model, relating the
new and base parameters of TG at the changing of the number
of the stator slots is created. A Lua script, providing the numerical-field calculations of the TG electromagnetic parameters in the FEMM software environment is worked out. Construction of the constructive and calculation models, the numerical-field calculations and delivery of results are performed by a computer automatically, that ensures high efficiency of the TG design process. Practical value. The considered version of the TG modernization on the example of
changing the number of the stator core slots provided an opportunity for the presentation of the principle of construction
and implementation of design synthesis system. For the practical use in the TG designing process, the developed and presented system can be more detailed with specifying the individual components of the mathematical model and expanded
for varying other parameters of TG and optimizing its design